Cluster de desempenho para mecanismos de segurança em redes - Rampanelli, Renan Luiz (2018)
The goal of this project is to implement a security system, which uses open source software, low cost and low power hardware, high availability and load balancing. For this, a research was carried out on the presented concepts and a case study referring to the tools that will be used. The results show the inefficiency of the proposed model, indicating that for the correct implementation of a load balance system, it would be necessary to use a greater amount of equipment than planned, thus increasing the value and complexity of the project.